Renewing dialogue and the repercussions of the contemporary Iraqi Arab reality (Journal of the College of Basic Education, 2023)
The renewal of dialogue (as a practice, tool, and method in dealing with the other) is one of the most important challenges facing the Iraqi and Arab intellectual today in the midst of his attempt to play his active and influential role as a tool for change and cultural movement in the Arab and Eastern societies. Where constructive dialogue has declined and the logic of one-party prevailed at times and political and religious violence at other times.What we want by dialogue is the conversation that takes place between two parties on a specific topic and with limited goals, and it may end with a known result that convinces the two parties or is accepted by both parties. It includes a method of dealing with the other, understanding him, and allowing him to express his opinion, hear this opinion, and discuss it. Dialogue is a methodology whose goal is to transform disagreement into a peaceful practice, reject violence, allow room for pluralism, contrast, and coloration, and give the other the right to participate and express oneself. Therefore, it is a method of understanding and a method of presenting opinions and dealing with people. And things to include all aspects of life.